The Effect of Interactive Video-Based Learning on Students’ English Learning Outcomes - Sucipto; Sam Hermansyah; Yuliyanah Sain; Titin Rahmiatin Rahim (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The integration of technology in language teaching has become increasingly important to enhance student engagement and learning outcomes. This study examined the effect of interactive video-based learning on students’ English learning outcomes at SMA N 2 Kulisusu Utara, Southeast Sulawesi. Employing a one-group pretest-posttest pre-experimental design, the research involved the entire population of 17 students in Class XI. Interactive videos, developed using Canva and Edpuzzle with embedded quizzes, subtitles, and interactive tasks aligned with the 2022 Merdeka Curriculum, were implemented over eight weeks. English learning outcomes were measured through a validated achievement test covering vocabulary mastery, grammar, reading comprehension, and listening skills. Data were analysed using paired sample t-test with SPSS version 26. The results showed a significant improvement in students’ English learning outcomes after the intervention (pretest mean = 64.12, SD = 8.45; post-test mean = 81.76, SD = 7.23; t = 9.87, p < 0.001). Additionally, students reported high positive perceptions toward the learning media. These findings indicate that interactive video-based learning is an effective and engaging instructional strategy for improving English proficiency in senior high school settings, particularly in resource-limited madrasah environments. The study recommends wider adoption of interactive video technology and further research with larger samples and control groups.